The single-strand DNA-binding protein SSB1 is involved in the expression of salivary gland radiation injury repair - Wang, Xian; Wang, Yuetong; Zeng, Xianglin; Lu, Haoyu; Mo, Dongqin; Li, Yuetao; Liu, Zhiqing; Huang, Yude; Yu, Kun; Wang, Daiyou (Frontiers in Pharmacology, 2024)
Objectives Single-strand DNA-binding protein 1 (SSB1) plays a crucial role in the cellular response to DNA damage. This study aimed to explore the expression and regulation of SSB1 in normal rat salivary gland tissues and tissues following radiation, with a specific emphasis on its involvement in the repair of salivary gland injury. Methods A total of 45 adult SD rats were randomly assigned to one control group or eight experimental groups. In the control group, five rats were euthanized without irradiation, and their parotid gland tissues were collected for analysis. The experimental groups received a dose of 6 Gy of radiation targeting the head and neck region; subsequently, five rats from each group were euthanized hly to collect parotid gland tissue samples, resulting in a total of eight experimental groups. The expression levels of SSB1, γ-H2AX, and PARP1 in the parotid gland tissues were assessed via immunohistochemistry, while changes in SSB1 gene expression were quantified via RT-qPCR. Results No significant morphological differences were observed between the two groups following HE staining. In the immunohistochemistry (IHC) analysis, notable tissue-specific variation in SSB1 expression was identified, with higher levels detected in the ducts than in the acini and connective tissue. The expression of SSB1 gene initially increased post-radiation before subsequently decreasing, ultimately returning to baseline levels, as corroborated by the RT-qPCR results. In contrast, γ-H2AX and PARP1 exhibited minimal expression in the control group; however, their expression peaked at 1 h in the experimental group before gradually declining to levels comparable to those of the control group. Conclusion Radiation induces time-dependent upregulation of SSB1 expression in rat salivary glands, indicating that SSB1 may play a role in radiation-induced repair processes.